2006
DOI: 10.1007/s11365-006-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

Role stress and entrepreneurship research

Abstract: Entrepreneurship as a domain of research has grown by benefiting from more established disciplines. However, a commonality in the early stages of applying established theories to entrepreneurship is the lack of grounded research frameworks. This paper reviews literature on role stress and develops a conceptual framework that illustrates how this construct can serve entrepreneurship research. Based on a review of psychological and sociological literature, the paper proposes a model of antecedents and consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 118 publications
0
30
0
1
Order By: Relevance
“…Emotional exhaustion is generally seen as close indicator of traditional stress reactions and has been related to both job stressors and to negative work and health outcomes (Lee and Ashforth 1990;Demerouti et al 2001). Recent works have suggested that burnout is a significant concern for entrepreneurs (Wincent & Örtqvist 2009b;Wincent et al 2008;Fernet et al 2016;C. D. Shepherd et al 2010).…”
Section: Justice Perceptions and Emotional Exhaustionmentioning
confidence: 99%
“…Emotional exhaustion is generally seen as close indicator of traditional stress reactions and has been related to both job stressors and to negative work and health outcomes (Lee and Ashforth 1990;Demerouti et al 2001). Recent works have suggested that burnout is a significant concern for entrepreneurs (Wincent & Örtqvist 2009b;Wincent et al 2008;Fernet et al 2016;C. D. Shepherd et al 2010).…”
Section: Justice Perceptions and Emotional Exhaustionmentioning
confidence: 99%
“…This is likely to activate inhibition, which means that these individuals are less likely to feel the positive feelings of passion while being attentive to threats and more exposed to constraints. In the entrepreneurship setting, work-family conflicts have been reported as detrimental to the entrepreneurial experience and positive perceptions of necessary risks in venturing (Wincent and Örtqvist, 2009). The entrepreneurs who spend more time on the business are likely to experience greater resource loss and perceive that demands are exceeding the resources.…”
Section: Time Spent On the Businessmentioning
confidence: 99%
“…Moreover, women may perceive disadvantages in the self-employment option (ie. pregnancy and maternity leave, role stress) in comparison with being an employee (Rouse 2005;Wincent and Ortqvist 2008). Another reason might be the fact that women have fewer female role models (Stewart et al 1998).…”
Section: Attitudementioning
confidence: 99%